Penerapan Model Pembelajaran Reading Guide Berbasis PAIKEM dalam Upaya Meningkatkan Motivasi Belajar Siswa di SDN 2 Cakranegara - Asni, Asni (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2017)
This study aims to determine the effectiveness of the application of PAIKEM Based Learning Guide Model in an effort to improve the learning activities of Class III.A Elementary School Students 2 Cakranegara. Benefits of this research is as a study material and material findings in the implementation of the learning process in the real class. For teachers to improve competence in the learning process and for learners to improve learning motivation that impacts the increase of learning outcomes of learners. This research is conducted two cycles, each cycle activity is; planning, execution, observation and reflection. The final result of action in cycle II shows that teacher observation result got average score (4.57) and result of observation learners reach average score (4,40). While the result of the increase of learners' learning activity is the increase of learners achievement result reaches the mean value (84,03), meaning the success indicator (> 70,00) has been exceeded. Because the success indicator has been proven that the research is successful and stopped in cycle II.